2020
DOI: 10.1007/s11356-020-08965-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of zinc oxide nanoparticles on arsenic stress in rice (Oryza sativa L.): germination, early growth, and arsenic uptake

Abstract: This study describes the role of zinc oxide nanoparticles (ZnO NPs) in alleviating arsenic (As) stress in rice (Oryza sativa) germination and early seedling growth. Seeds of rice were primed with different concentrations (10, 20, 50, 100, and 200 mg L −1) of ZnO NPs and As (0, and 2 mg L −1) for 12 days in petri dishes. Two milligrams per liter of As treatment represented a stress condition, which was evidenced by germination rate, seedling length, seedling dry weight, chlorophyll, superoxide dismutase (SOD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…At the same time, it can be inferred from Fig. 6 that when the amount of nZnO applied is greater than 100 mg kg − 1 , the As concentration in the shoots and roots will be further reduced, because more As will be adsorbed before entering the rice root, similar to our previous stuy [ 29 ]. But it also needs to be noted that high concentration of nZnO can cause poison to plants and reduce the biomass of rice.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…At the same time, it can be inferred from Fig. 6 that when the amount of nZnO applied is greater than 100 mg kg − 1 , the As concentration in the shoots and roots will be further reduced, because more As will be adsorbed before entering the rice root, similar to our previous stuy [ 29 ]. But it also needs to be noted that high concentration of nZnO can cause poison to plants and reduce the biomass of rice.…”
Section: Discussionsupporting
confidence: 79%
“…1 ). Our early germination experiments also showed that low concentration of nZnO (10, 20 mg/L) amendment increased the shoot length by 13.1–14.1% and shoot weight by 15.1–41.2%, respectively [ 29 ]. It’s reported that kinds of NPs increase the growth of plants under metal stress.…”
Section: Discussionmentioning
confidence: 96%
“…1). Our early germination experiments also showed that low concentration of nZnO (10, 20 mg/L) attendment increased the shoot length by 13.1-14.1% and shoot weight by 15.1-41.2%, respectely [29]. It's reported that kinds of NPs increase the growth of plants under metal stress.…”
Section: Discussionsupporting
confidence: 66%
“…Besides plant protection, these smart NPs are extensively used to regulate the physiological process. For example, SiO 2 NPs (silicon dioxide NPs) elevates seed germination rate in Lycopersicon esculentum [ 71 , 72 ], chitosan-polymethacrylic-NPK increase biomass, nutrient uptake and antioxidant enzymes in Phaseolus vulgaris [ 73 , 74 ], Au-NPs (gold NPs) promotes seed germination, seedling growth, enzymatic activity and nutrient uptake in Zea mays [ 75 , 76 ], SiO 2 -NPs improve uptake of NPK, increase enzymatic activity and seed germination rate in Hyssopus officinalis and Z. mays [ 77 79 ], chitosan-CuNPs (copper NPs) enhance seed germination, activation of α-amylase, protease and activity of various antioxidant enzymes in Z. mays [ 2 , 80 , 81 ], chitosan-ZnNPs (zinc NPs) increase accumulation of zinc content and defense enzymes in Triticum durum [ 82 , 83 ], chitosan-γ-polyglutamic acid-gibberellic acid NPs promotes seed germination, root development, leaf area, hormonal efficiency, extracellular enzymes and nutrient efficiency [ 83 , 84 ], Chitosan-polymethacrylic acid-NPK NPs promotes protein content and nutrient uptake [ 74 , 85 ], ZnO-NPs (zinc oxide NPs) increase activity of catalase (60.7%), superoxide dismutase (22.8%) and nutrient acquisition [ 86 , 87 ], CeO 2 -NPs (cerium oxide NPs) enhance seed germination and vigour, enzymatic activity and nutrient uptake in Spinacia oleracea and Z. mays [ 88 91 ], AuNPs increase chlorophyll content and antioxidant enzyme activities in Brassica juncea [ 92 ] and TiO 2 NPs (titanium oxide NPs) enhance chlorophyll content, nutrient uptake, activity of Rubisco and antioxidant enzymes in S. oleracea and Cicer arietinum [ 89 , 93 ] (Table 1 ).…”
Section: Nanoformulations As a Promising Tool In An Agricultural Systemmentioning
confidence: 99%